An investigation into the method of energy monitoring and reduction for machining systems. (October 2020) - Hu, Luoke; Zheng, Hao; Shu, Lianjie; Jia, Shun; Cai, Wei; Xu, Kangkang
Highlights: A five-dimension model for energy consumption of machining systems is developed. The automatic acquisition of energy data is driven by Radio Frequency IDentification. Virtual spaces interact with physical spaces to calibrate the machining energy simulation. Abstract: Improving the energy efficiency of machining systems (MSs) is an urgent and challenging issue in sustainable manufacturing. Considering the dynamics and uncertainty of MSs, a five-dimension model is developed to monitor and reduce the energy consumption (EC) of MSs. In this model, the automatic acquisition of EC data from physical MSs is driven by Radio Frequency IDentification (RFID) read events. The EC service model provides monitoring and scheduling services for reducing the EC of physical MSs by connecting with virtual MSs in real time. The procedures of the EC reduction method for the MSs are presented. A case study of MSs for auto parts was conducted to illustrate the proposed method. The results showed that the time and EC of MSs were reduced by 148 s and 49.67 KJ, respectively.